Baicalin Promotes Mammary Gland Development via Steroid-Like Activities - Chen, Weizhen; Wei, Wei; Yu, Liya; Zhang, Xin; Huang, Fujing; Zheng, Qiping; Wang, Lingli; Cai, Cheguo (Frontiers in Cell and Developmental Biology, 2021)
Baicalin, the main flavonoid component extracted from Scutellaria roots, has a variety of biological activities and is therefore used in the treatment of many kinds of diseases. However, whether baicalin affects the normal development of tissues and organs is still unclear. Here, using a mouse mammary gland model, we investigated the effects of baicalin on the expansion of mammary stem cells (MaSCs) and mammary development, as well as breast cancer progression. Interestingly, we found that baicalin administration significantly accelerates duct elongation at puberty, and promotes alveolar development and facilitates milk secretion during pregnancy. Furthermore, self-renewal of MaSCs was significantly promoted in the presence of baicalin. Moreover, in a tumor xenograft model, baicalin promoted tumor growth of the MDA-MB-231 cell line, but suppressed tumor growth of the ZR-751 cell line. Mechanistically, baicalin can induce expression of the protein C receptor, while inhibiting the expression of the estrogen receptor. Transcriptome analysis revealed that baicalin is involved in signaling pathways related to mammary gland development, immune response, and cell cycle control. Taken together, our results from comprehensive investigation of the biological activity of baicalin provide a theoretical basis for its rational clinical application.